2020
DOI: 10.1002/saj2.20071
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of measuring procedure of farmland soils using laser‐induced breakdown spectroscopy

Abstract: Laser‐induced breakdown spectroscopy (LIBS) is an emerging multi‐elemental analytical technique offering fast and simultaneous quantification of soil properties with minimal sample preparation and effective cost. Due to soil heterogeneity, spectral variation however limits the quantitative robustness. In this study, 348 soil samples were collected and prepared for acquisition of LIBS spectra. Influences of shot layer and number on LIBS quality were evaluated by spectral intensity and relative standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Consequently, variations in the spectra at each site are significantly different, which is mainly responsible for the low repeatability of LIBS analysis (Wainner, Harmon, Miziolek, McNesby, & French, 2001). To optimize the LIBS measuring procedure, spectral normalization and calibration or prediction modeling are effective ways to improve accuracy, as found in our previous study (Xu et al., 2020). We concluded that in‐depth effort is needed to overcome the poor accuracy caused by spatial variations in the soil.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Consequently, variations in the spectra at each site are significantly different, which is mainly responsible for the low repeatability of LIBS analysis (Wainner, Harmon, Miziolek, McNesby, & French, 2001). To optimize the LIBS measuring procedure, spectral normalization and calibration or prediction modeling are effective ways to improve accuracy, as found in our previous study (Xu et al., 2020). We concluded that in‐depth effort is needed to overcome the poor accuracy caused by spatial variations in the soil.…”
Section: Introductionmentioning
confidence: 79%
“…The soil tablets were placed over an X–Y–Z manual–automatic micrometric platform with a 1.0‐μm stage of travel at every coordinate. According to the optimized soil measuring procedure (Xu et al., 2020), the LIBS spectra of soils for predicting SOM were collected at five depths with a 5‐ by 5‐mm window cut. The soil spectra of the deepest shot layer are the best for predicting SOM, according to Xu et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations